Deeper Than The Dead: Vera Boyett # 1 - Webb, Debra (Seattle : Thomas & Mercer, 2024)
When the remains of her long-missing stepmother are discovered in a cave on her family$1 (Bs land in Tennessee, Vera Boyett, a crime analyst and newly disgraced deputy police chief, must return home and face her past.s
new book 2025 winter.
Keywords: Women detectives -- Fiction; Summer -- Fiction; Sisters -- Fiction; Stepmothers -- Fiction; Missing persons -- Investigation -- Fiction; Murder -- Investigation -- Fiction; Secrecy -- Fiction; Tennessee -- Fiction; Detective and mystery fiction; Thriller fiction; Detective fiction; Mystery fiction